2018
DOI: 10.3389/fmicb.2018.00659
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities of Diatoms Display Strong Conservation Across Strains and Time

Abstract: Interactions between phytoplankton and bacteria play important roles in shaping the microenvironment surrounding these organisms and in turn influence global biogeochemical cycles. This microenvironment, known as the phycosphere, is presumed to shape the bacterial diversity around phytoplankton and thus stimulate a diverse array of interactions between both groups. Although many studies have attempted to characterize bacterial communities that associate and interact with phytoplankton, bias in bacterial cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
108
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 79 publications
11
108
1
Order By: Relevance
“…To investigate the effect of long term culturing on the associated bacterial communities, A. ostenfeldii (strains 13-20) and A. minutum/ tamarense (strains 21-28) isolates were monitored after 6 and 4 months of culturing respectively. Similar to studies of diatoms in culture (Schäfer et al, 2002;Behringer et al, 2018), the bacterial communities of the Alexandrium isolates is this study were shown to be consistent over time (Supporting Information Table S1 and Fig. S8).…”
Section: Culture Conditionssupporting
confidence: 83%
See 2 more Smart Citations
“…To investigate the effect of long term culturing on the associated bacterial communities, A. ostenfeldii (strains 13-20) and A. minutum/ tamarense (strains 21-28) isolates were monitored after 6 and 4 months of culturing respectively. Similar to studies of diatoms in culture (Schäfer et al, 2002;Behringer et al, 2018), the bacterial communities of the Alexandrium isolates is this study were shown to be consistent over time (Supporting Information Table S1 and Fig. S8).…”
Section: Culture Conditionssupporting
confidence: 83%
“…There are several considerations that should be made before drawing conclusions about in situ associations from in vitro conditions (Sala et al, 2005;Garcés et al, 2007;Hattenrath-Lehmann and Gobler, 2017;Behringer et al, 2018). For example, culture conditions and time in culture can have significant impacts as culturing can alter the bacterial community composition within hours (Sapp et al, 2007;Weissbach et al, 2010).…”
Section: Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides short‐term associations, different diatoms establish long‐term specific relationships with selected bacteria, creating a stable community unique for each species across strains. This situation suggests control of the associated microbiome based on chemical signalling (Behringer et al ., ). The involvement of chemical compounds in this process was further demonstrated by documenting community shifts in bacterioplankton after addition of organic matter derived from different phytoplankton species (Tada et al ., ).…”
Section: Interkingdom Interactions Shape Population Dynamicsmentioning
confidence: 97%
“…In this way, different types of interactions were discovered, which were either microbial population driven or dictated by individual bacterial organisms. Recently, Behringer et al (2018) demonstrated that bacterial communities on diatom surfaces displayed strong conservation across diatom strains. Seymour et al (2017) elegantly summarized the main corresponding mechanisms and processes, which show an impressive array of diversity and complexity.…”
Section: Introductionmentioning
confidence: 99%